Association between prognostic nutritional index and all-cause mortality in critically ill patients with ventilator-associated pneumonia: a retrospective study based on MIMIC-IV database - Ji, Wenwen; Wang, Guangdong; Liu, Jia (Frontiers in Nutrition, 2025)
BackgroundVentilator-associated pneumonia (VAP) remains a significant clinical challenge in the ICU due to its high mortality rate. The Prognostic Nutritional Index (PNI), a composite biomarker based on serum albumin levels and total lymphocyte counts, reflects nutritional and immune status, but its prognostic significance in VAP patients remains unclear. This study evaluated the association between PNI and mortality in critically ill patients with VAP.MethodsWe retrospectively analyzed data from 1,457 patients diagnosed with VAP from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Patients were grouped according to PNI quartiles and an identified optimal threshold. Cox regression, restricted cubic spline (RCS) analysis, and subgroup analyses were conducted to evaluate associations between PNI and 30-day and 90-day all-cause mortality.ResultsAmong 1,457 critically ill patients with VAP, the all-cause mortality rates were 23.68% at 30 days and 34.32% at 90 days. Patients in the highest PNI quartile exhibited significantly reduced mortality risks compared with the lowest quartile, with an adjusted HR of 0.60 (95% CI, 0.44–0.81) for 30-day mortality and 0.64 (95% CI: 0.50–0.82) for 90-day mortality. RCS analysis revealed a significant non-linear “L”-shaped relationship between PNI and mortality (p < 0.001). Below the threshold, patients with higher PNI had significantly lower risk of 30-day mortality (HR = 0.93, 95% CI: 0.91–0.95) and 90-day mortality (HR = 0.94, 95% CI: 0.92–0.96).ConclusionA higher PNI at ICU admission was independently associated with lower short-term and long-term mortality in critically ill VAP patients. Routine assessment of PNI could enable early identification of high-risk patients and guide targeted nutritional and immunological interventions.